Impacts of industrial actions, protests, strikes and lockouts by health and care workers during COVID-19 and other pandemic contexts: a systematic review - Isabel Craveiro; Pradeep Kumar Choudhury; Ana Paula Cavalcante de OLiveira; Alessandra Pereira; Inês Fronteira; Raphael Chança; Giorgio Cometto; Mario Roberto Dal Poz; Paulo Ferrinho (BMC, 2024)
Abstract Background Public health emergencies of international concern (PHEICs) as the COVID-19 pandemic and others that have occurred since the early 2000s put enormous pressure on health and care systems. This is being a context for protests by health and care workers (HCWs) because of additional workload, working conditions and effects on mental and physical health. In this paper, we intended to analyze the demands of HCWs associated with industrial actions, protests, strikes and lockouts (IAPSLs) which occurred during COVID-19 pandemic and other PHEICs; to identify the impact of these grievances; and describe the relevant interventions to address these IAPSLs. Methods We included studies published between January 2000 and March 2022 in PubMed, Embase, Scopus, BVS/LILACS, WHO's COVID-19 Research Database, ILO, OECD, HSRM, and Google Scholar for grey literature. Eligibility criteria were HCWs as participants, IAPSLs as phenomenon of interest occurring in the context of COVID-19 and other PHEICs. GRADE CERQual was used to assess risk of bias and confidence of evidence. Results 1656 records were retrieved, and 91 were selected for full-text screening. We included 18 publications. A system-wide approach, rather than a limited approach to institutions on strike, makes it possible to understand the full impact of the strike on health and care services. PHEICs tend to aggravate already adverse working conditions of HCWs, acting as drivers for HCWs strikes, leading to staff shortages, and financial issues, both in the North and in the Global South, particularly evident in Asia and Africa. In addition, issues related to deficiencies in leadership and governance in heath sector and lack of medical products and technologies (e.g., lack of personal protective equipment) were the main drivers of strikes, each contributing 25% of the total drivers identified. Conclusions It is necessary to focus on the preparedness of health and care systems to respond adequately to PHEICs, and this includes being prepared for HCWs' IAPSLs, talked much in the context of COVID-19 pandemic. Evidence to assist policymakers in defining strategies to respond adequately to the health and care needs of the population during IAPSLs is crucial. The main impact of strikes is on the disruption of health care services' provision. Gender inequality being a major issue among HCWs, a proper understanding of the full impact of the strike on health and care services will only be possible if gender lens is combined with a systemic approach, rather than gender-undifferentiated approaches limited to the institutions on strike.